Thermal analysis (TG–DSC, DSC–microscopy and EGA) and characterization of heavy trivalent lanthanides and yttrium isonicotinates - Nunes, W. D.G. [UNESP]; Teixeira, J. A. [UNESP]; do Nascimento, A. L.C.S. [UNESP]; Ekawa, B. [UNESP]; Ionashiro, M. [UNESP]; Caires, F. J. [UNESP] (Springer Nature, 2019)
The trivalent lanthanide isonicotinates were synthesized to obtain stoichiometry Lu(IN) 3 and Ln(IN) 3 ·2H 2 O (Ln = Tb to Lu, and Y; IN = isonicotinate). A deep study of the thermal behavior in oxidant (air) and inert (N 2 ) atmospheres was carried out using the following thermoanalytical techniques: simultaneous thermogravimetry and differential scanning calorimetry (TG–DSC), differential scanning calorimetry (DSC) and evolved gas analysis (EGA by TG–DSC–FTIR). From these results, it was possible to determine that dehydration occurs in a single step and the thermal decomposition of the anhydrous compounds occurs in one or two (air), and two or three steps (N 2 ). The final residues of thermal decomposition were Tb 4 O 7 and Ln 2 O 3 (Ln = Dy to Lu, and Y) in air atmosphere, while in N 2 atmosphere the mass loss is still being observed up to 1000 °C. The identified gaseous products evolved during the thermal decomposition in dynamic dry air and nitrogen atmospheres were water, CO 2 , pyridine and CO. From these thermoanalytical data, it was possible to propose a general equation of thermal decomposition of these compounds in the N 2 atmosphere. DSC curves of Tb and Ho compounds presented endothermic peaks corresponding to a reversible phase transition, confirmed by powder X-ray diffractometry (XRD), not previously reported. In addition, infrared vibrational spectroscopy (IR) suggests the coordination through carboxylate as bridging bidentate ligand toward the heavy trivalent lanthanides metals. This paper is complementary to our previous study involving the series of light trivalent lanthanides isonicotinates.
Keywords: Evolved gas analysis; Isonicotinates; Lanthanides; Thermal analysis